Bibliometrik Sustainability Report pada Perbankan Indonesia: Tren Publikasi dan Perspektif Masa Depan - Hidhayati, Annisa Tri; Rahmi, Audina; Nadiar, Rahmi; Noor Hayatie, Marliza; Alfikri, Rahmatullah (Politeknik Piksi Ganesha Indonesia, 2025)
Using a bibliometric approach, this study analyzes the development of scientific publications related to Sustainability Reports in the Indonesian banking sector in the last five years (2020–2024). The analysis was conducted on 124 articles obtained through the Publish or Perish (PoP) software and analyzed using VOSviewer. The results of the study show that the trend of publications regarding Sustainability Reports has increased significantly every year. Bibliometric visualization also indicates a shift in research focus from merely disclosing Sustainability Reports to integrating sustainability into business strategies, green financial product innovations, and the environmental impact of banking policies. The direction of Sustainability Report research in the future is predicted to develop into a more in-depth study related to its influence on banking business strategies, the effectiveness of implementing sustainable financial policies, and how this industry can mitigate environmental and social risks. In addition, sustainability issues in the context of digital banking and financial technology (fintech) are also predicted to become part of academic studies that are developing along with increasing innovation in the financial sector.